Microinsurance Potential and Rural Economic Empowerment: A SWOT Analysis of MSMEs - Panisa Panisa; Yenni Samri Juliati Nasution; Fauzi Arif Lubis (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study analyzes the potential of microinsurance implementation to enhance the economic empowerment of rural communities in Singkuang Village, Muara Batang Gadis District, Mandailing Natal Regency. The research background is based on the condition of the majority of MSMEs, who still face business risks without adequate financial protection. The study used a qualitative approach with a case study design, through interviews, observation, and documentation, as well as a SWOT analysis. The results show that MSMEs' internal strengths outweigh their weaknesses (IFAS 3.541 > 3.103) and opportunities outweigh their threats (EFAS 3.157 > 2.264), placing MSMEs in Quadrant I (aggressive strategy). Microinsurance is considered relevant because it offers affordable premiums, simple administration, and fast claims, while also encouraging a culture of risk management. However, challenges remain in the form of low financial literacy and limited access to information. Therefore, education, mentoring, and support from the government and financial institutions are needed. Overall, the implementation of microinsurance has great potential to strengthen business resilience and rural economic empowerment if accompanied by increased literacy, access to capital, and accessible product distribution.